Prognostic value of procalcitonin in pneumonia: A systematic review and meta‐analysis - Liu, Dan (Respirology, 2015)
This meta‐analysis was performed to determine the accuracy of procalcitonin (PCT) in predicting mortality in pneumonia patients with different pathogenic features and disease severities. A systematic search of English‐language articles was performed using PubMed, Embase, Web of Knowledge and the Cochrane Library to identify studies. The diagnostic value of PCT in predicting prognosis was determined using a bivariate meta‐analysis model. The Q‐test and I (2) index were used to test heterogeneity. A total of 21 studies comprising 6007 patients were included. An elevated PCT level was a risk factor for death from community‐acquired pneumonia (CAP) (risk ratio (RR) 4.38, 95% confidence interval (CI) 2.98–6.43), particularly in patients with a low CURB‐65 score. The commonly used cut‐off, 0.5 ng/mL, had low sensitivity (SEN) and was not able to identify patients at high risk of dying. Furthermore, the PCT assay with functional SEN <0.1 ng/mL was necessary to predict mortality in CAP in the clinic. For critically ill patients, an elevated PCT level was associated with an increased risk of mortality (RR 4.18, 95% CI: 3.19–5.48). The prognostic performance was nearly equal between patients with ventilator‐associated pneumonia (VAP) and patients with CAP.